The foundations of Buddhism - Gethin, Rupert; Ohio Library and Information Network (Oxford, Oxford University Press, 1998)
Buddhism is a vast and complex religious and philosophical tradition with a history that stretches over 2,500 years, and which is now followed by around 115 million people. In this introduction to the foundations of Buddhism, Rupert Gethin concentrates on the ideas and practices which constitute the common heritage of the different traditions of Buddhism (Thervada, Tibetan, and Eastern) which exist in the world today. From the narrative of the story of the Buddha, throughdiscussions of aspects such as textual traditions, the framework of the Four Noble Truths, the interaction between the monas
Cover; Contents; List of Tables and Figure; List of Maps; A Note on Buddhist Languages; INTRODUCTION; 1. THE BUDDHA: THE STORY OF THE AWAKENED ONE; 2. THE WORD OF THE BUDDHA: BUDDHIST SCRIPTURES AND SCHOOLS; 3. FOUR TRUTHS: THE DISEASE, THE CAUSE, THE CURE, THE MEDICINE; 4. THE BUDDHIST COMMUNITY: MONKS, NUNS, AND LAY FOLLOWERS; 5. THE BUDDHIST COSMOS: THE THRICE-THOUSANDFOLD WORLD; 6. NO SELF: PERSONAL CONTINUITY AND DEPENDENT ARISING; 7. THE BUDDHISM PATH: THE WAY OF CALM AND INSIGHT; 8. THE ABHIDHARMA: THE HIGHER TEACHING; 9. THE MAHAYANA: THE GREAT VEHICLE
"Opus"--Cover
Includes bibliographical references (pages [302]-318) and index
Keywords: Buddhism; Religion